Partners' limited: limited liability in partnerships structure: an overview of the common law and the Shariah - Abd Ghadas, Zuhairah Ariff (LexisNexis Malaysia Sdn Bhd, 2009)
Unlimited liability of partners is undoubtedly the hallmark of partnerships structure/laws. This principle emphasises on partners having collective responsibilities for debts and liabilities of the firm. The extent of unlimited liability of partners in partnership includes their personal assets. The principle of unlimited liability in partnership is constantly criticised because it impose heavy obligation and high business risk upon partners. As business expands and the firm gets bigger, it is more difficult for partners to know each other and what more to trust them to the extent of bearing each other's liabilities. The concept of unlimited liability may be appropriate for small and family partnerships whereby partners know each other but in big and international firms where partners are mostly strangers, it is not practical to apply unlimited liability. In recent years, the partnerships structure/laws went through rapid changes from mere general partnership to limited partnership ('LP'), limited liability partnership ('LLP') with a separate legal entity and LLP with a status of body corporate. Under the Islamic law, partnerships structure (sharikah) has an established reputation and clear recognition as a valid business vehicle. The application of limited liability in sharikah is also well established and clearly justified. This paper intends to highlight the development of common law partnerships structure/laws with a special reference to the application of limited liability. The Islamic perspectives are deliberately included to highlight the apparent possibilities of implementing limited liability in partnerships structure.